How Does El Niño–Southern Oscillation Change Under Global Warming—A First Look at CMIP6. Issue 22 (17th November 2020) - Fredriksen, Hege‐Beate; Berner, Judith; Subramanian, Aneesh C.; Capotondi, Antonietta
Abstract: The latest generation of coupled models, the sixth Coupled Models Intercomparison Project (CMIP6), is used to study the changes in the El Niño–Southern Oscillation (ENSO) in a warming climate. For the four future scenarios studied, the sea surface temperature variability increases in most CMIP6 models, but to varying degrees. This increase is linked to a weakening of the east‐west temperature gradient in the tropical Pacific Ocean, which is evident across all models. Just as in previous generations of climate models, we find that many characteristics of future ENSO remain uncertain. This includes changes in dominant time scale, extratropical teleconnection patterns, and amplitude of El Niño and La Niña events. For models with the strongest increase in future variability, the majority of the increase happens in the Eastern Pacific, where the strongest El Niño events usually occur. Plain Language Summary: The El Niño–Southern Oscillation (ENSO) is a naturally occurring irregular oscillation in the tropical Pacific Ocean alternating between warm (El Niño) and cold (La Niña) phases every 2–7 years. The sea surface temperature anomalies associated with ENSO are linked to variability in key climate quantities, such as temperature, winds, and precipitation over many parts of the globe. Hence, it is of great scientific and societal interest to determine how ENSO may change in a warming climate. We find that the latest generation of climate models shows changes in ENSO in a warmer world. The future variability is increasing, especially in the eastern equatorial Pacific, where the extreme warm events usually occur. This increase appears to be related to a reduced temperature difference between the eastern and western equatorial Pacific. The global weather patterns influenced by both the warm and cold events will also change, but models disagree on how large these changes will be. Key Points: Changes in El Niño–Southern Oscillations are detected for future projections in the latest generation of climate models Models agree on future decrease of the equatorial zonal temperature gradient, which facilitates conditions for stronger El Niño events El Niño and La Niña global teleconnection patterns shift in the future, but there is a large uncertainty on the magnitude of the change